Novel mutation of the NOTCH3 gene in Arabic family with CADASIL - Saeed Bohlega (MDPI AG, 2011)
Mutations in the NOTCH3 gene are responsible for cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), an adult onset hereditary angiopathy leading to ischemic stroke, vascular dementia and psychiatric disorders. All mutation of NOTCH3 described so far are striking stereotyped leading to the gain or loss of cystiene residue in a given epidermal growth factor (EGF), like repeat. We report an Arabic family affected with CADASIL mutation, G1790 C, in Exon 11 of the NOTCH3 gene. This is the first novel mutation reported in Arabic CADASIL patients. This finding confirms that mutations in NOTCH3 are associated with the pathogenesis of CADASIL across different ethnic background.